Pertanggungjawaban Pidana Pelaku Pencabulan terhadap Anak yang Dilakukan oleh Anak Ditinjau dari Undang-Undang Perlindungan Anak & Sistem Peradilan Pidana Anak - Taufiq Ramadhan; Dewi Pika Lbn Batu (Prodi Ilmu Hukum, Universitas Teuku Umar, 2023)
Children are subjects that cannot be separated from the survival of humans, the nation and the state because children are the next generation of the nation. In line with the rapid development of the times and supported by several factors of juvenile delinquency, low intelligence, minimal education, bad association of children and the mass media (shows that tend to be unfavorable) are the causes of a crime. Crimes that are mostly committed by children, for example sexual abuse. This study aims to determine the process of criminal justice against children who are in conflict with the law and to find out about the criminal responsibility of perpetrators of sexual abuse of children committed by children. The nature of the research used is analytical descriptive with a normative juridical approach. The criminal justice process for children in conflict with the law is carried out by prioritizing the concept of restorative justice to protect juvenile offenders which is currently adopted in Law No. 11 of 2012 concerning the juvenile justice system through the diversion system. Criminal responsibility for children as subject actors must prioritize the principles of protection, justice, non-discrimination, the best interests of the child, respect for the child's opinion, continuity and development of the child, guidance and guidance for children, the principle of proportionality, deprivation of liberty and punishment for children is an effort final or ultimum remedium.Â Keywords: Criminal Liability, Children, Obscenity